High HIV/STI prevalence among cisgender men and transgender women sex workers attending community-based centres in Barcelona, Spain: The Sweetie Project. (October 2022) - Ferrer, Laia; González, Victoria; Martró, Elisa; Folch, Cinta; Saludes, Verónica; Muñoz, Rafael; Rodríguez, Vanesa; Morales, Adriana; Meroño, Mercè; Morey, Francisca; Sanjosé, Sílvia de; Casabona, Jordi
Background: The aim of this study was to describe the socio-demographics, and the sexual and health-seeking behaviours of cisgender men and transgender women sex workers (M & TWSW) attending community-based organisations (CBOs) in Barcelona, Spain, as well as to estimate the prevalence of HIV, hepatitis B virus (HBV), hepatitis C virus (HCV), Chlamydia Trachomatis (CT) and Neisseria gonorrhoeae (NG) among them at different anatomical sites. Methods: The Sweetie Project was a community-based cross-sectional study of 147 M & TWSW recruited in two CBOs in Barcelona between 2017 and 2018. A nurse collected biological samples from rectum, pharynx and urethra from the subjects at each CBO and the participants self-completed an epidemiological questionnaire. Results: The highest prevalence observed was for HIV infection (25.3%) followed by bacterial STIs (NG 19.2% and CT 10.3%). The most prevalent anatomical site was pharyngeal (17.7%) followed by rectal (13.8%). More than half of participants who had a pharyngeal infection presented an isolated pharyngeal infection (57.7%) and half of those who had a rectal or urethral infection presented an isolated infection respectively. The seroprevalence of HCV and HBV was 2.4% and 34.2% respectively. There was a poor but statistically significant correlation between HIV and rectal CT infection ( r = 0.31), previous exposure to HCV ( r = 0.27) or self-reported STI ( r = 0.23), as well as between previous exposure to HCV and rectal CT ( r = 0.21) or self-reported STI ( r = 0.20). Discussion: The Sweetie Project confirms the high burden of HIV and bacterial STIs among a sample of M&TWSW recruited in CBOs and reinforces the need to routinely screen them at all exposed anatomical sites.